The Andalusian Artistic Influences on Religious Buildings of in TheMaghrib Central The Zayanian Period - ayache, mohamed (Journal of Social Sciences and Humanities, 2021)
The reign of BaniZian in the Middle Maghreb(633-962/1235-1554) building a collection of university mosques with distinctive architectural styleAlthough most of its monuments have been wiped out, the city to thisday is still the artistic influences of Andalusia,In this article we will try to illustrate the most important architectural influences of Andalusia that are exotic to the buildingArchitecture, decoration as is the case for the SidiBelhasan Mosque (696/1296), Mosque of WledImam (710/1310)and Sidi Ibrahim Mesmoudi (764/1363), Relying on descriptive analytical field studies and citing previous sources and research, With the artistic relationship between Andalusian architecture, The Zayan mosque architecture and the historical roots of this artistic current in both the Almoravid and Almohad periods,There was a cohesion between them and the features of this model emerged through the architectural and decorative elements that were met architecturally and artistically by the artist Zayani,With the historical roots of this artistic current being demonstrated during the Era of the Almoravids and Almohads,Fromthere, weraise the followingproblem:What are the mostprominent manifestations of Andalusianartistic influences in the Zayanimosque architecture?Whattopicsdidtheycover?Wewilltry to answerthisproblem, highlighting the generalcharacteristics, the main features and the features of the general planning on which the Zayanimosquesweredesigned, This iswhywe have divided the subject of ourresearchintotwo main axes, the first axis includes planning and building materials (bricks, mortar, molasses, marble and wood),The second includes architectural elements (minarets, domes, doorways, roofing, support, columns, crowns, arches and niches),This issupported by artistic images, forms and charts,Weconcluded in thisresearchthat the Zayanimosques in Tlemcen wereaffected by twoartisticcurrents, one by Sharqi, its center of Kairouan, the otherAndalusian and its center in Cordoba,It wasfusedinto a local architectural art formthatwas an authentic architectural character of the region, whichwas made up of the Moroccan-Andalusian style,All of thiswillbeaddressed in somedetail in thisstudy, focusing on andalusianartistic influences on the aforementionedZayanimosque buildings.